Facing infant cuteness: how nurturing care motivation and oxytocin system gene methylation are associated with responses to baby schema features - Spencer, Hannah; Parianen Lesemann, Franca H.; Buisman, Renate S. M.; Kraaijenvanger, Eline J.; Branje, Susan; Boks, Marco P. M.; Bos, Peter A. (Hormones and behavior, 2024)
Baby schema features are a specific set of physical features—including chubby cheeks, large, low-set eyes, and a large, round head—that have evolutionary adaptive value in their ability to trigger nurturant care. In this study among nulliparous women (N = 81; M age = 23.60, SD = 0.44), we examined how sensitivity to these baby schema features differs based on individual variations in nurturant care motivation and oxytocin system gene methylation. We integrated subjective ratings with measures of facial expressions and electroencephalography (EEG) in response to infant faces that were manipulated to contain more or less pronounced baby schema features. Linear mixed effects analyses demonstrated that infants with more pronounced baby schema features were rated as cuter and participants indicated greater motivation to take care of them. Furthermore, infants with more pronounced baby schema features elicited stronger smiling responses and enhanced P2 and LPP amplitudes compared to infants with less pronounced baby schema features. Importantly, individual differences significantly predicted baby schema effects. Specifically, women with low OXTR methylation and high nurturance motivation showed enhanced differentiation in automatic neurophysiological responses to infants with high and low levels of baby schema features. These findings highlight the importance of considering individual differences in continued research to further understand the complexities of sensitivity to child cues, including facial features, which will improve our understanding of the intricate neurobiological system that forms the basis of caregiving behavior.
Online verfügbar: 6. Juli 2024, Artikelversion: 6. Juli 2024
Gesehen am 04.03.2025